The effects of the flipped classroom model designed according to the ARCS motivation strategies on the students' motivation and academic achievement levels - Karabatak, Songul; Polat, Hakan (Springer, 2020)
This study aimed to determine the effects of the traditional classroom model, distance education model and flipped classroom model designed according to ARCS (attention, relevance, confidence and satisfaction) motivation strategies on motivation and academic achievement levels. For this purpose, the study was conducted by using an experimental pretest-posttest control group design. Purposive sampling was used to determine the participants. Frequency, percentage, mean, dependent groups t-test and ANOVA test were utilized for data analysis. The results indicated that the academic achievement levels of the students in the flipped classroom model using ARCS motivation strategies were significantly higher than those of the students in the distance education classroom model and the traditional classroom model. In addition, the training process did not lead to a significant change in the motivation of the students in the traditional classroom model and distance education classroom model, but did lead to a significant change in the motivation of the students in the flipped classroom model. In response to the results of the study, various suggestions were made.
Keywords: ARCS motivation strategies; Academic achievements; Traditional classroom; Distance education; Flipped classroom